Pengujian Pinhole Dan Analisis Erodibilitas Pada Tanah Lempung Untuk Bahan Timbunan Dekat Sungai - Mahmudi, Agus; Wardoyo, Tri; Suryaningrum, Anis (Fakultas Teknik Universitas Bhayangkara Surabaya, 2025)
ABSTRACT Things that can influence soil to experience erosion include the nature of the distribution and erodibility of the soil. The level of soil erodibility is determined based on the structure, texture, permeability and organic matter content of the soil. The material tested in the pinhole testing in this case is clay material which will be used as embankment material for the Merauke PLTGM project, Papua. This test aims to classify whether the material is included in the dispersive (D) or nodisoercive (ND) clay category, while the aim is to determine the value of the erodobiolity coefficient K. This test uses the SNI-03-3405 method. What is observed in this test is the water discharge and turbidity of the water coming out of the testing equipment. From laboratory tests and analysis of the test results that have been carried out, the value of K = 0.19 is obtained, while the soil classification is in the D2 clay category. Keywords: diversive and Erodibility